Otorhinolaryngology consultations in a multidisciplinary hospital — their effects on residents training on floor - Ambreen Abdullah Unar; Muhammad Hammad Deewani; Muhammad Sohail Awan; Syeda Amrah Hashmi; Abdul Basit Shah Vardag; Ainulakbar Mughal (Journal of the Pakistan Medical Association, 2022)
Objective: To determine all types and severity of Otolaryngology consultation requests at our tertiary care center and spectral records of problems related to otorhinolaryngology come across initially by residents which will help in re-shaping residency programmes and enhance patient related care. Methodology: All otorhinolaryngology consultation received over a three-month period were recorded prospectively. Information collected for each encounter included the time, date, reason for consult at primary service and admission with final ENT diagnosis, any surgical or non-surgical intervention, and basic patient demographics. Results: A total of 127 consults for inpatients were reviewed from April 2020 to June 2020. Out of total, 84 (66.1%) patients were male and 43 (33.8%) were females. Adult patient consultations amounted to 87(68.5%) while 18(14.1%) were in the age range of 6-18 years. Only 4(3.1%) consultations were raised for neonatal patients. Continuous...